Психолого-педагогічні особливості формування підлітків як суб’єктів дослідницької діяльності - Буднік, Світлана Василівна; Budnik, Svitlana V. (Вісник Чернігівського національного педагогічного університету, 2014)
Актуальність теоретичного обґрунтування психолого-педагогічних особливостей виховання суб’єктності підлітків в процесі дослідницької роботі обумовлена сенситивністю визначеного вікового періоду для розвитку суб’єктної позиції школярів у процесі дослідницької діяльності. Relevance of theoretical study concerning psychological and pedagogical features of teenagers’ subjectivity education in the process of research activity is conditional on sensitivity of the certain age period for development of pupils’ subject position in the research activity. Purpose of this paper is to outline the psychological and pedagogical features of teenagers’ education as subjects of research activity. The author emphasized that an important fact in formation of a teenager as a subject of research activity was consideration of cognitive motivation and research activity, their intellectual abilities, characteristics of analytical and critical thinking; development of tendency to introspection and self-analysis; wide use of subjective experience in interpretation and evaluation of facts, phenomena, events, reality, dedication bots caused by deep interest in scientific problems. It is noted that the subject of research activity is a teenager, capable of independent search of subjectively unknown knowledge, learning the lessons of creativity and achieving subjectively new research findings. An important role in formation of a teenager as a subject of research activity is assigned to leading role of a teacher.
Psychological and pedagogical features of forming teenagrs as subjects of research activity
Роботу виконано на кафедрі теорії і методики природничо-математичних дисциплін початкової освіти
Keywords: суб’єкт; дослідницька діяльність; підліток; subject; teenager; research activity